PENGEMBANGAN DAN PENDAMPINGAN UMKM MELALUI DIGITALISASI USAHA, BRANDING DAN PACKAGING UNTUK UMKM CAMILAN IBU NUR DI KELURAHAN SUKAWANA - Surachman, Surachman; Riska, Riska; Nurfadillah, Nurfadillah; pamungkas, Bintang Putra; Febrianti, Cantika Berliana (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
This activity is the result of a community service program through KKM-T which aims to develop Ibu Nur's Snack UMKM in Sukawana Village, Curug District, Serang City. The main problem identified was the owner’s limited understanding of digital marketing strategies and their application. The methods employed included problem identification, digital marketing assistance, and product rebranding. The activities carried out involved creating social media accounts and designing a new logo for Camilan Ibu Nur. This program is expected to improve business performance and competitiveness, enabling sustainable growth through digitalization.